P45 Practical use of the DECAF score: Can we improve outcomes in acute exacerbation of COPD admissions?. (12th November 2015) - Collier, L; David, T; Craig, C; Yadavilli, R
Abstract : Background: Acute exacerbations of COPD (AECOPD) are the second most common cause of emergency hospital admission in England and are associated with an inpatient mortality rate of 4.3%. 1 The Dyspnoea, Eosinopenia, Consolidation, Acidaemia and Atrial Fibrillation (DECAF) Score, is an effective prognostic tool that predict mortality in AECOPD admissions. This scoring system is easy to apply during admission and has performed better than existing prognostic tools. 2 We aim to appraise the efficacy of DECAF score in our busy respiratory and medical admissions unit. Method: Hospital admissions with AECOPD from Dec 2014 to Mar 2015 are prospectively reviewed and DECAF score applied to each patient. Morbidity and mortality indicators were then correlated with both total DECAF scores and each predictive index. Results: 78 admissions were reviewed, 60% were male and the mean age was 72.7 years. Average length of stay was 15.3 days and 12 patients died in hospital. Our results were comparable with previous studies 3, with inpatient mortality highest in those with DECAF scores of 3–5 (92%) and lowest in those with scores of 0–1 (0%). Higher DECAF scores were also associated with use of non-invasive ventilation (43%). Furthermore, each individual predictive index within the DECAF score was independently related to an increased mortality rate. There was 44% mortality in patients with atrial fibrillation and 30% mortality in patients with dyspnoea score of eMRC 5B. In-hospital mortality rate increased with each DECAF score (Figure 1 ). Conclusions: Introduction of DECAF score as clinical prediction tool for AECOPD admissions in our departments may be beneficial in reducing morbidity and mortality. Those scoring highest should be considered for early escalation, higher level of care and or palliative management. Those with lower scores may be suitable for early supported discharge. Further study of a larger group however is advisable to confirm the significance of these findings. References: 1 National Chronic Obstructive Pulmonary Disease Audit Programme: Clinical audit of COPD exacerbations admitted to acute units in England and Wales, 2014 2 J Steer, J Gibson, S Bourke. The DECAF Score: predicting hospital mortality in exacerbations of chronic obstructive pulmonary disease. Thorax 2012;67 :970–976